Orientalism : a reader - Macfie, A. L. (Edinburgh University Press, 2000)
"In the period of decolonisation that followed the end of the Second World War a number of scholars, mainly Middle Eastern, launched a sustained assault on Orientalism -- the theory and practice of representing 'the Orient' in Western thought -- accusing its practitioners of misrepresentation, prejudice and bias. As a result an intense debate occurred regarding the validity of the charges made, involving not only Orientalists but students of history, anthropology, sociology, women's studies and the media. Orientalism: A Reader provides the student with a selection of key readings from this debate, covering a range of areas including myth, imperialism, the cultural perspective, Marxist interpretation and feminist attitudes. The origins and character of the debate on Orientalism are introduced, as well as the intellectual foundations of the assault made and the nature of the debate which ensued. Coverage begins with nineteenth-century material from thinkers such as Hegel and Marx, and moves through extracts from Nietzsche, Gramsci and Foucault to contemporary work from, for example, Bryan Turner, John MacKenzie and Edward Said. As well as a general introduction, each section is introduced and the extracts are placed in context to guide the student carefully through this complex debate."--